Body creams and electric screwdrivers: how counter-stereotypical but trivial tasks trigger gender identity threat - Jiménez-Moya, Gloria; SanMartín, Ana N.; Carvacho, Héctor (Frontiers in Psychology, 2025)
Traditional gender roles are fixed social norms that dictate what men and women should and should not do. These gender patterns have prejudicial consequences for both men and women. As such, reducing support for and approval of gender roles is a crucial goal in our societies. Exposure to counter-stereotypical role models and interventions showing men and women in cross-gendered roles seems to be an efficient way of reducing the impact of traditional gender norms. However, holding a cross-gendered position might trigger negative backlash in terms of identity. In this work, we test the effect of a common and simple counter-stereotypical choice on the emergence of gender identity threat. Participants (N = 493) who were forced to choose a counter-stereotypical product for themselves (a body cream or an electric screwdriver) showed compensatory gender-system defense responses. Men who experienced gender identity threat subsequently expressed higher levels of sexism, whereas women under threat showed greater support for the traditional feminine stereotype. These results suggest that even counter-stereotypical everyday and trivial tasks can trigger a gender identity threat that, in turn, leads to attitudes that justify and perpetuate gender inequality.